A Step Forward Progress in Physics and Cosmology with an Alternative Approach to General Relativity (Global Journal of Science Frontier Research, 2020)
A property of spacetime which is the ability for more space to come into existence was first discovered by Albert Einstein with his General Theory of Relativity (GTR). This theory had predicted some observations like gravitational waves, black holes, orbital movements etc. Another property of spacetime is the fact that empty space can possess its own energy. As more space comes into existence, more of this energy of space appears, this form of energy regarded as dark energy would cause the universe to expand and accelerate at a fast rate. GTR had predicted some cosmological observations we see today but its still unable to account for the nature of dark energy, this has resulted into theorists insisting that there could be something wrong with GTR and a new theory could include a field that creates this cosmic acceleration.
Keywords: space; dark energy; energy; fabric; universe